«Quando verrà …» (Mt 25,31): su un passo del Gadla Libānos - Bausi, Alessandro (Aethiopica, 2003)
This short note is devoted to the interpretation of the passage of Gadla Libānos (whose critical edition and translation, together with that of the Miracles, is forthcoming) which assumedly attributes to the saint the translation of the Gospel of Matthew. To the contrary of the interpretation given in the book under press (due to editorial decision), it is maintained here that the passage records a different tradition, according to which Baqlā was the place where some particular sections only (Mt 5,1 ff. and 25,31 ff.), and not the whole Gospel of Matthew, were written. The sections of the Gospel are indicated in the passage under examination by their incipits (probably corresponding to their tituli), exactly as in a passage from the Miracles of Libānos. Some linguistic considerations on the value of the conjunction ʾama seem to confirm the hypothesis here advanced.